The Association of Polymorphisms in Interleukin-6 (IL-6), Interleukin-10 (IL-10), IL-6 Receptor, and IL-10 Receptor Genes with the Risk of Pediatric Inflammatory Bowel Disease - Krawiec P; Lejman M; Pac-Kożuchowska E (Journal of Inflammation Research, 2025)
Paulina Krawiec,1 Monika Lejman,2 Elżbieta Pac-Kożuchowska1 1Department of Pediatrics and Gastroenterology, Medical University of Lublin, Lublin, 20-059, Poland; 2Independent Laboratory of Genetic Diagnostics, Medical University of Lublin, Lublin, 20-059, PolandCorrespondence: Paulina Krawiec, Department of Pediatrics and Gastroenterology, Medical University of Lublin, Racławickie 1, Lublin, 20-059, Poland, Tel +48817185420, Email paulina.krawiec@umlub.plPurpose: Inflammatory bowel disease (IBD) results from a complex interplay between genetic, immune, and environmental factors. Despite a significant advancement in genetic studies, until now, little is known about genotype–phenotype correlations in children with IBD. Thus, we aimed to evaluate if polymorphisms in the Interleukin-6 (IL-6), Interleukin-10 (IL-10), IL-6 receptor, and IL-10 receptor genes are associated with the risk for pediatric IBD, its phenotype and severity.Patients and Methods: We enrolled 50 children with IBD in the study group and 20 healthy children to the control group. Demographic and clinical data of the subjects were collected from available electronic medical records. The DNA was extracted from peripheral blood samples of all individuals. TaqMan® single nucleotide polymorphism (SNP) genotyping assays were used to detect IL-10 variants RS3024505 and RS1800872, IL-10RA RS3135932, IL-10RB RS2834167, IL-6 RS10499563, and IL-6R RS4537545. A binary logistic regression model was used to evaluate the association between SNP’s and the risk of IBD, IBD onset, phenotype, and the need to use of steroids or biologics.Results: There was a significant difference in the genotype distribution of IL-6 RS10499563 between patients with IBD and control group (χ 2 = 10.96, p = 0.004). The distribution of genotype CT at IL-6 RS10499563 was higher, whereas the distribution of genotype CC and TT at IL-6 RS10499563 was lower in children compared to controls. There were no significant differences in the distribution of the other SNPs between the study and control groups. We found a significant association between the genotype CT at IL-6 RS10499563 and the risk of ulcerative colitis (OR 13.41; 95% CI: 1.58– 114.26; p = 0.02), but not Crohn’s disease (OR 7.60; 95% CI: 0.82– 70.16; p = 0.07).Conclusion: In this study, we found a significant association between the genotype CT at IL-6 RS10499563 and the risk of ulcerative colitis in children.Keywords: Crohn’s disease, ulcerative colitis, children, genetics